Quantity versus quality: Effects of argumentation in bad news letters - Frank Jansen; Daniel Janssen (Journal of Writing Research, 2013)
Do the quality and the quantity of arguments have an impact on the evaluation of bad news messages? To answer this question, two experiments were carried out using bad news letters in which the quality and the quantity of the arguments were manipulated in a contextually realistic way. The results of both experiments show that adding argumentation has a positive impact on the perceived politeness and the persuasive force of the letters. Furthermore, the studies show that the impact of strong arguments is greater than that of weak arguments. The effect of adding successive arguments is positive as well. However, the results indicate that one or two arguments are sufficient. Adding a third argument only minimally contributes to better evaluations.